Grammatisation and changes in Turkish language teaching in the 19th and 20th centuries: mood and tense in textbooks - Okten, C. E.; Sauner-Leroy, M. H. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
The development and diffusion of written media in the Ottoman world resulted in further dissemination of education, which led to several competitive methodological attempts in the teaching of the Turkish language. The development of grammar and dictionaries became the tools of the new state's educational policies. As Arabic was the focus of language education in the classical Ottoman world, the grammar of Ottoman Turkish was first analysed through Arabic categories and definitions. Greco-Latin grammatical categories, which classified morphological items and syntactic segments, helped to create categories in order to facilitate the simplification and the standardisation of grammar, substantially supported by the state. In this study, we examine the process of grammatisation of the Turkish language and the switch between two grammatisations, from extended Arabic grammar to extended Latin grammar. By examining a corpus of 28 manuals, we try to clarify the transformation of teaching methods, from the 19th to the 20th century, with a particular focus on tenses and moods. We conclude that some ambiguity regarding the description of Turkish grammar and its terminology still persist due to emerging new versions of extended grammar categories.
Keywords: Ottoman Turkish; Turkish grammar; grammar textbooks; grammatisation; moods; tenses; Extended Arabic grammar; Extended Latin grammar; History; Linguistics